The World Parliament of Religions, the Swami, and the Evangelist: Contextualizing Late 19th-Century American Responses to Hinduism - Anne Richards (Journal of Global Initiatives, 2018)
This article explores how Hinduism and other religions and philosophies outside the Christian traditions were received by Americans influenced by secularism, science, globalization, and expanding U.S. imperialism in the late 19th century. The article also explores the role of two missionaries, John Henry Barrows and Swami Vivekananda, arguably the most influential participants in the World Parliament of Religions of 1893.